A Systematic Literature Review on Ethics and Artificial Intelligence in the World of Business and Accounting (2024-2025) - Susan Cornelya Hermina; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The development of Artificial Intelligence (AI) has brought fundamental transformations to business and accounting practices, improving work efficiency, analytical accuracy, and organizational governance. However, these advancements also raise critical questions regarding ethics, professional responsibility, and human resource readiness. This study aims to conduct a Systematic Literature Review (SLR) of recent literature concerning the relationship between ethics, technology readiness, and AI implementation in business and accounting contexts. The review maps empirical and conceptual studies from 2024-2025, including research conducted in Vietnam, Lebanon, and Indonesia. The findings reveal that AI adoption success is influenced by technology readiness, perceived usefulness, and ease of use, yet it also heavily depends on ethical culture and organizational governance. Previous studies tend to overlook the role of moral factors, data transparency, and ethical oversight in AI implementation. Therefore, this study emphasizes the need for integration between digital ethics and technology readiness as a foundation for sustainable AI development in business and accounting.